Leapfrogging in Marketing: Empirical Analysis of Kenyan Mobile Phone Industry - Chepkoech, Mae; Lagat, Charles; L. Frankwick, Gary (SEISENSE (PRIVATE) LIMITED, 2021)
Purpose: This paper aims to analyze the concept of leapfrogging in the mobile phone industry in the Republic of Kenya. Design/Methodology: The study adopted a cross-sectional research design, stratified and simple random sampling techniques in collecting data from 349 respondents picked from a population of 15506 employees of three Cosmopolitan County Governments in Kenya. Findings: Outcome indicates that; perceived product quality and perceived switching cost positively and significantly influence intentions to Leapfrog. However, the urgency to replace does not influence choices to leapfrog. Originality/value: The study findings bring a new understanding of the determinants of consumer leapfrogging and their intentions to leapfrog in the mobile phone industry and highlight the role perceived product quality and switching cost play in determining intention leapfrog.